2021
DOI: 10.1002/clc.23738
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of pulmonary congestion detection by lung ultrasound in patients with chronic heart failure

Abstract: Chronic heart failure is one of the common causes of hospitalization and death. Pulmonary congestion is the common disease feature of patients with chronic heart failure, which could be correctly diagnosed by lung ultrasound. Efficacy of lung ultrasound‐guided pulmonary congestion management for patients with acute heart failure is well documented, however, more evidence is needed to establish the clinical value of pulmonary congestion detection by lung ultrasound examination in patients with chronic heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
6
0
2
Order By: Relevance
“…Pulmonary congestion (PC) is one of the major characteristics of HF [ 6 , 7 , 8 ]. The importance of PC in the disease course of HF has been confirmed by numerous clinical trials, and the presence of PC is shown to be associated with a significantly increased risk of mortality and rehospitalization in HF patients [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary congestion (PC) is one of the major characteristics of HF [ 6 , 7 , 8 ]. The importance of PC in the disease course of HF has been confirmed by numerous clinical trials, and the presence of PC is shown to be associated with a significantly increased risk of mortality and rehospitalization in HF patients [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eksempelvis er hjerteinfarktpasienter en utsatt gruppe til å få postinfarkt hjertesvikt med utvikling av lungeødem. Tidlig ultralyd og faste rutiner ved hjelp av fokusert ultra lyd kan guide og bedre pasientbehandlingen (44,45). Pleuravaeske og lungestuvning er således et tegn på hjertesviktforverring, men kan vaere utfordrende å oppdage uten bruk av ultralyd, grunnet lite fremtredende symptomer (45)(46)(47)(48).…”
Section: Diskusjonunclassified
“…The number of A lines and gray zones need not be taken into account while changing medication because there was no causal link between pulmonary congestion and the lung's ultrasonography B-Lines and A-Lines. The B-lines, a marker of lung congestion, might be semi-quantitatively quantified by lung ultrasonography (11). (Figure 1) illustrates the thoracic ultrasonography points method for the detection of pulmonary congestion.…”
Section: Clinical Applications and Significance; Reflection From Lite...mentioning
confidence: 99%